Comparison of self-compassion, hardiness, forgiveness in women with hypertension and normal subjects - Shirinzadeh Dastgiri , Samad; Latifi , Maryam; Daneshmand, Nasibeh; Alavenejad, Narjes Alsadat; Samimipoor, Mahboubeh; Mirzaei , Zahra (Applied Family Therapy Journal (AFTJ), 2020)
Aim: Background and purpose: Blood pressure is one of the most important causes of chronic disability in the world, which has chronic and progressive causes. The present study was conducted with the aim of comparing self-compassion, stubbornness and forgiveness in hypertensive patients and normal people. Method: The research design was of the type of causal-comparative research and the statistical population of the present study was female patients with blood pressure referred to the clinics of Shiraz city as well as normal people. A number of 100 people including two groups of 50 people of high blood pressure patients and normal people were selected as a sample, and high blood pressure patients who were under the supervision of a doctor due to blood pressure problems and visited the clinic and had the conditions to participate in the research were selected from them to conduct the research, Was invited Hypertensive patients were selected by targeted sampling from among those who referred to the clinics. Also, normal people were selected by available sampling method, the sample people were matched based on demographic characteristics such as age, education, and marital status. The measurement tools in this research were: Rees, Pamir, Neff and Vangacht (2011) self-compassion questionnaire short form, Ahvaz Psychological Toughness Scale (AHI) - and forgiveness questionnaire by Ray, Levikano, Flak, Olivski, Heim and Madia (2001). The data were analyzed using multivariate analysis of variance and Spss.22 software. Results: The results of analysis of variance indicated that there was a significant difference between self-compassion (F=94.72; P<0.001) in hypertensive and normal patients. Also, there was a significant difference between stubbornness (F=43.78; P<0.001) in hypertensive and normal patients, and based on other results, a significant difference was observed between positive feelings (F=15.99; P<0.001) and negative feelings in hypertensive and normal patients. Conclusion: Medical specialists related to blood pressure can consider the stress factor and pathological psychological characteristics of patients that can be related to the risk of occurrence and recurrence of this disease. Advise their patients to consult a psychologist and complete at least one complete course of psychotherapy related to psychosomatic diseases.